Kedudukan Dan Kewenangan Komisi Yudisial Republik Indonesia Dan Perbandingannya Dengan Komisi Yudisial Di Beberapa Negara Eropa - -, Suparto (UI Scholars Hub, 2017)
Reformation has given birth to the amendment on 1945 Constitution. One of the results of the third amendment of the constitution was the birth of Judicial Commission. The standing of Judicial Commission is very important, so structurally it is being positioned at the same level with the Supreme Court and the Constitutional Court. Yet, the Judicial Commission role is as an auxiliary body to the judicial power institutions. It only deals with the matters of honor, dignity, and behavior of the judges, not the judiciary institutions. Aside from that, Judicial Commission is not involved in the organization, human resources, administration, and the financial matters of the judges. It is different with the European countries’ judicial commissions. The author proposes that Judicial Commission of the Republic of Indonesia should adopt or emulate European judicial commissions, which then adapted with Indonesian judiciary system.